Separator Plate

A carbon-enhanced separator plate with a continuous conductive network addresses the issues of cost and stability in fuel cells and batteries, achieving low resistance and reduced thickness for improved efficiency and cost-effectiveness.

JP2024517579A5Active Publication Date: 2025-02-05SGL CARBON SE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023560707
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-03-31
Filing Date
2022-03-22
Publication Date
2025-02-05
Estimated Expiration
2042-03-22

AI Technical Summary

Technical Problem

Existing separator plates in proton exchange membrane fuel cells and redox flow batteries face issues of high cost due to the use of precious metals for corrosion protection or mechanical instability with carbon-based plates, leading to increased thickness and weight, which affects structural integrity and efficiency.

Method used

A single-layer carbon-enhanced separator plate with a continuous conductive carbon network, using carbon fiber fabric and a thermosetting resin, and optionally filled with carbon black or graphite, to achieve mechanical stability and low contact resistance.

Benefits of technology

The solution results in a mechanically stable separator plate with low contact resistance, reduced thickness, and improved conductivity, enhancing the efficiency and reducing material costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention relates to a separator plate, a method for manufacturing a separator plate, and uses of the separator plate.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a separator plate, a method for manufacturing a separator plate, and uses of the separator plate. [Background technology]

[0002] The separator or bipolar plates in proton exchange membrane (PEM) fuel cells, phosphoric acid fuel cells, or redox flow batteries are either metal-based or carbon-based. Metal plates are very stable and can be made very thin (<0.2 mm), but the metal needs to be protected from corrosion and therefore extend the service life of the entire system. Metal plates are often coated with precious metals or carbon / graphite to protect them from corrosion. This approach has the disadvantage of being very costly. Carbon-based plates do not have corrosion problems, but are mechanically unstable and therefore have a large wall thickness, generally greater than 0.6 mm. A large wall thickness adversely affects the construction volume and weight of the entire system, thereby increasing costs due to high material production costs and high material usage. In addition, it is advantageous if the separator plates can be manufactured as an infinite material, as the final product is installed in large numbers, thereby reducing production costs.

[0003] Carbon fiber paper is known as a primary product for gas diffusion layers in fuel cells or redox flow batteries, for example as described in US Pat. No. 5,399,663. The method described therein can be carried out in a continuous process. The carbon fiber paper is impregnated with a phenolic resin slurry and then carbonized or graphitized (see embodiment 1 of US Pat. No. 5,399,663). The carbon fiber paper, as well as the first intermediate product after the slurry impregnation and carbonization / graphitization, are very porous, i.e. very permeable, and have low mechanical stability. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] European Patent No. 1369528 Summary of the Invention [Problem to be solved by the invention]

[0005] SUMMARY OF THE PRESENT EMBODIMENT It is therefore an object of the present invention to provide a separator plate, and its manufacture and use, that overcomes the above-mentioned shortcomings of the prior art. [Means for solving the problem]

[0006] The problem is a separator plate, thermosetting This is achieved by providing a separator plate comprising a single layer of resin-impregnated carbon fiber reinforced carbon, having a continuous conductive carbon network, a thickness of less than 0.5 mm, preferably 0.1 to 0.3 mm, and a tensile strength of greater than 30 MPa, preferably greater than 35 MPa, and particularly preferably greater than 45 MPa.

[0007] In the context of the present invention, a continuous conductive network is understood to refer to an uninterrupted network.

[0008] The thickness of the separator plate is understood to refer to the wall thickness, and a thickness of less than 0.5 mm is advantageous because it is mechanically stable enough, weighs less, and therefore requires less structural mass in the layer structure of the entire fuel cell. A tensile strength of more than 30 MPa means that the separator plate is mechanically stable enough, and therefore can be manufactured and operated with a small thickness. A thickness of more than 0.5 mm means that contact The resistance becomes so great that the entire fuel cell becomes inefficient.

[0009] According to the present invention, the separator plate comprises: contact Resistance is 8mΩcm 2 less than 5 mΩcm 2 less than 3 mΩcm, particularly preferably 2 is less than. contact Resistance is 8mΩcm 2 If it is greater than , the resistive losses will be too large and the fuel cell will be inefficient, e.g., will heat up excessively. contact The measurement of resistance is described below.

[0010] The separator plate advantageously has a density of 1.7 g / cm 3 preferably less than 1.4 g / cm 3 and particularly preferably less than 1.3 g / cm 3 Density is less than 1.7g / cm 3 If it is greater than 100 mm, the disadvantage of the resulting separator plate being heavy is detrimental.

[0011] According to the invention, the carbon fiber reinforced carbon comprises a single layer of woven carbon fiber with carbon binder bridges between the carbon fibers, which form a continuous conductive network, resulting in a particularly thin and high tensile separator plate due to the fiber reinforcement, which still has good electrical conductivity.

[0012] Advantageously, the carbon fibre fabric is taken from the group of carbon fibre paper, carbon fibre non-woven fabrics, carbon fibre fabrics or stable fibre fabrics.

[0013] In the production of carbon fiber paper, a slurry of aqueous short carbon fiber binder mixture is deposited on a screen in a paper machine. After a drying step, the short cut fibers are combined with each other and the carbon fibers are aligned within the plane of the paper in a planar orientation (2-dimensional structure). Carbon fiber nonwovens, on the other hand, are 3-dimensional structures produced by wet or dry storing short fibers, which are produced by a mechanical reinforcement process using needles or water jets. Carbon fiber fabrics are woven fabrics with at least two yarn systems that do not run parallel and therefore cross. Staple fiber fabrics are woven yarns made from stretch-cut and twisted filaments.

[0014] According to the present invention, thermosettingThe resins include those from the group of epoxy resins, phenolic resins, furan resins or benzoxazine resins.

[0015] thermosetting The resin closes the pores of the carbon fiber fabric while maintaining electrical conductivity based on the carbon network, thereby increasing its density and mechanical strength.

[0016] Advantageously, thermosetting The resin includes a dispersed filler.

[0017] The filler is selected from the group of carbon black, expanded graphite, natural or synthetic graphite, ground carbon fiber, or mixtures thereof. The filler can further increase the electrical conductivity since the continuous conductive carbon network is further expanded by the filler. Depending on the morphology of the filler particles, the filler can also have a favorable effect on the density of the separator plate, for example by preventing the formation of pores due to better wetting of the impregnating carbon network, or by forming a toothed layer as a gas barrier in case of platelet-like anisotropic morphology.

[0018] According to the present invention, the mass fraction of the filler is 0% by mass to 40% by mass, preferably 5% by mass to 20% by mass, and particularly preferably 8% by mass to 15% by mass. If it is less than 5% by mass, the electrical conductivity is not high enough, and if it is more than 40% by mass, the viscosity becomes high, which causes a problem in the completeness of impregnation.

[0019] Advantageously, the cross section of the separator plate has a concentration gradient of the filler. This means that the filler can remain mainly on the surface, forming a concentration gradient, depending on the size and morphology of the particles. This means that there is a higher concentration of filler in the outer region of the separator plate and a lower concentration of filler in the inner region of the separator plate. The concentration gradient depends on the type of filler, especially the particle size. By having the filler remain mainly on the surface, the separator plate becomes more dense, improving electrical conductivity and reducing contact resistance.

[0020] The separator plate advantageously has a permeability coefficient of 5×10 -5 cm 2 / s, preferably less than 1×10 -5 cm 2 / s. The permeability coefficient is less than 5×10 -5 cm 2 / s, the separator plate is considered a technically dense separator plate, i.e., its technical density meets the requirements for use as a separator plate for the respective different gas or liquid spaces.

[0021] According to the present invention, thermosetting The surface of the resin-impregnated carbon fiber reinforced carbon is structured. This structuring allows the targeted and controlled supply of gas / liquid and the removal of reaction products that may occur. Furthermore, this structuring can be used for water cooling of the stack structure.

[0022] Another subject of the invention is a method for manufacturing a separator plate, comprising the following steps: a) providing a carbon fiber fabric b) impregnating the carbon fiber fabric with a carbon donor c) high-temperature treatment of the impregnated carbon fiber fabric in an inert gas atmosphere at temperatures above 1300° C., preferably above 1700° C., particularly preferably above 2000° C. d) thermosetting Providing a resin system e) the carbon fiber reinforced carbon obtained in step c) provided in step d) thermosetting Impregnating the resin system f) curing and pressing the resin impregnated carbon fiber reinforced carbon from step e) under a pressure of 1-50 bar.

[0023] In the context of the present invention, the carbon donor in step b) is understood to refer to a resin with a carbon yield of more than 20% by weight, which may additionally be loaded with carbon, graphite or carbon black. The inert gas atmosphere is understood to refer to a nitrogen or argon atmosphere. The impregnation steps b) and e) can be carried out on one side or on both sides. thermosetting The impregnation with the resin system and the curing and pressing in steps e) and f) increase the density and mechanical strength of the carbon fiber reinforced carbon, so that the separator plate can have a very thin construction.

[0024] Step f) can be followed advantageously by surface activation on both sides by grinding, explosion, chemical or plasma treatment, which can remove any electrically insulating layer (resin layer) that may be present on the separator plate.

[0025] Advantageously, 0% to 40% by weight, preferably 5% to 20% by weight, particularly preferably 8% to 15% by weight of filler is dispersed in the thermosetting resin system, which can further increase or improve the electrical conductivity and density.

[0026] The pressing step is advantageously carried out with a structured tool, the tool being understood to mean an embossing roller, a forming roller or a plate. The structured tool realises the deformation in the pressing step. The pressing step is carried out by: thermosettingThis allows the resin system to penetrate further into the carbon fiber fabric, and the filler, depending on the size of the particles, is allowed to remain mainly on the surface, forming a concentration gradient. This means that the separator plate has a concentration gradient in cross section that decreases from the outside to the inside of the separator plate on both sides of the separator plate. The concentration gradient depends on the type of filler, especially the particle size. Since the filler remains mainly on the surface, it can improve the electrical conductivity, reduce the contact resistance, and further increase the density of the separator plate.

[0027] According to the invention, the process can be carried out as a continuous or batch process, with continuous processes being particularly preferred.

[0028] Another subject is the use of the separator plates in redox flow batteries or fuel cells or as electrodes for electrostatic air cleaning devices.

[0029] The invention will now be described, purely by way of example, by way of an advantageous embodiment and with reference to the accompanying drawings, in which: [Brief description of the drawings]

[0030] [Figure 1] FIG. 1 shows a separator plate (4) comprising a single layer of carbon fiber reinforced carbon (1) containing a thermosetting resin (2). [Diagram 2] FIG. 1 shows a separator plate (4) comprising a single layer of carbon fiber reinforced carbon (1) containing a thermosetting resin (2) and a filler (3). [Diagram 3] FIG. 1 shows a separator plate (4) comprising a single layer of carbon fiber reinforced carbon (1) containing a thermosetting resin (2) and a filler (3). [Figure 4] FIG. 1 shows a scanning electron microscope (SEM) image of a single layer of carbon fiber reinforced carbon (1). [Diagram 5] FIG. 2 shows a micrograph of a separator plate according to the present invention. [Figure 6]Diagram 1: Contact resistance as a function of surface pressure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] Figure 1 shows thermosetting A separator plate (4) is shown comprising a single layer of carbon fiber reinforced carbon (1) impregnated with resin (2).

[0032] Figure 2 shows thermosetting A separator plate (4) is shown with a single layer of carbon fiber reinforced carbon (1) impregnated with resin (2) and having filler (3). Due to the properties of the filler, a concentration gradient is created that causes the filler to penetrate only slightly into the porous carbon fiber reinforced carbon (1).

[0033] Figure 3 shows thermosetting A separator plate (4) is shown with a single layer of carbon fiber reinforced carbon (1) impregnated with resin (2) and having filler (3). Due to the different particle sizes of the filler, the smaller particles penetrate further into the carbon fiber reinforced carbon (1) than the larger particles.

[0034] Figure 4 shows thermosetting Shown is an SEM image of porous carbon fiber reinforced carbon (1) before it was sealed with a resin system. The carbon binder bridges between the carbon fibers are clearly visible. The combination of the fibers and the binder bridges form a continuous conductive network.

[0035] FIG. 5 shows a micrograph of a separator plate according to the present invention having filler accumulation in the outer regions and a lower filler concentration towards the inside.

[0036] Diagram 1 is based on surface pressure contact Resistance is high initially (at low surface pressure) contact It becomes clear that the resistance does not only represent the pure material resistance, but also reflects a significant portion of the contact resistance. As the surface pressure increases, the contact resistance decreases and is measured. contactThe resistance is dominated by the contribution of material resistance. In the surface pressure range of 1 to 1.5 MPa, it is almost steady. contact A resistance level of 1 MPa is reached. The surface pressure level of 1 MPa corresponds roughly to the practical application conditions in a fuel cell stack. Diagram 1 shows embodiment 1 together with the reference measurements of the outer GDL (gas diffusion layer). It can be seen that the additional material layer of the separator plate only contributes a small part to the overall resistance of the sandwich layer structure including the two GDL layers.

[0037] The present invention will be described below using embodiments, but the embodiments do not represent the limitations of the present invention.

[0038] The separator plates can be manufactured as described below.

[0039] Measurement method contact resistance contact To obtain an application-relevant measurement of resistance, the resulting cured separator plate is measured in a layer sandwich similar to the configuration in a fuel cell between two gas diffusion layers (GDL 22BB, SIGRACET®). Using the following formula: contact Calculate the resistance Rz: Rz = ΔU·A / ΔI

[0040] ΔU is the voltage between the electrodes, A is the surface area of ​​the sample, and ΔI is the current.

[0041] The electrodes are coated with gold to avoid boundary resistance that may arise due to oxidized surfaces. During the measurements, different contact pressures are applied, ranging from 5 psi (US units) to 1.5 MPa, respectively, and the layer thickness is determined at the same time. To determine the influence of the additional material layer made of GDL 22BB, a reference measurement was performed with only two GDL 22BB layers. Since in this series connection the material resistances are additive, the material resistance of the sample can be determined as the difference between the resistance of the GDL 22BB / sample / GDL 22BB layer structure and the reference measurement of the two GDL 22BB layers.

[0042] Permeability coefficient The permeability coefficient is determined in accordance with DIN 51935:2019-06.

[0043] strength The strength was determined by tensile strength tests according to DIN EN ISO13934-1:2013-08. For standard-compliant tests, a beam of 160 mm length and a consistent width of 50 mm was used as the test specimen geometry, with a deviation from this a tapered specimen geometry, also 50 mm wide, with the same free crack length but with a clamping region 80 mm wide to avoid fracture within the clamping region.

[0044] density The geometric density was determined by applying weights to circular samples of 50 mm diameter.

[0045] A carbon fibre reinforced carbon monolayer can be produced, for example, as described in US Pat. No. 5,399,633.

[0046] Embodiment 1: A monolayer of carbon fiber reinforced carbon (1) (available under the name GDL 36 AA, SIGRACET®, from SGL Carbon GmbH) with a thickness of 225 μm (measured at a load of 5 psi) is coated on one side with a 180 μm thick epoxy resin film (2) using a film applicator, with 7% by weight of conductive carbon black (Super P, available from Imerys Graphite & Carbon) dispersed in the epoxy resin. The coated monolayer is then cured in a hot press at a pressure of 32.5 bar and 130° C. for 60 minutes.

[0047] At a pressure of 1MPa contact Resistance is 7.8mΩcm 2 The transmission coefficient is 2.2×10 -6 cm 2 / s. The thickness of the separator plate thus obtained is 210 μm (measured at a load of 5 psi). The geometric density is 1.14 g / cm 3 The tensile strength is 47 MPa.

[0048] EMBODIMENT 2 A single layer of carbon fiber reinforced carbon (1) (available under the name GDL 36 AA, SIGRACET® from SGL Carbon GmbH) with a thickness of 225 μm (measured at a load of 5 psi) is coated on both sides with a 130 μm thick epoxy resin film (2) in which 9% by weight of expanded graphite (Sigratherm® GFG5, available from SGL Carbon) is dispersed in the epoxy resin. The coated single layer is then cured in a hot press at a pressure of 32.5 bar and 130° C. for 60 minutes.

[0049] At a surface pressure of 1MPa contact Resistance is 7.7mΩcm 2 The transmission coefficient is 1.4×10 -5 cm 2 / s. The thickness of the separator plate thus obtained is 200 μm (measured at a load of 5 psi). The geometric density is 1.18 g / cm 3 The tensile strength is 39 MPa.

[0050] EMBODIMENT 3 A monolayer of carbon fiber reinforced carbon (1) (available under the name GDL 36 AA, SIGRACET®, from SGL Carbon GmbH) with a thickness of 225 μm (measured at a load of 5 psi) is coated on one side with a 180 μm thick epoxy resin film (2) using a film applicator, with 9% by weight of conductive carbon black (Super P, available from Imerys Graphite & Carbon) dispersed in the epoxy resin. The coated monolayer is then cured in a hot press at a pressure of 32.5 bar and 130° C. for 60 minutes.

[0051] At a pressure of 1MPa contact Resistance is 3.8mΩcm 2 The transmission coefficient is 5.5×10 -6 cm 2 / s. The thickness of the separator plate thus obtained is 202 μm (measured at a load of 5 psi). The geometric density is 1.04 g / cm 3 It is.

[0052] EMBODIMENT 4 A monolayer of carbon fiber reinforced carbon (1) (available under the name GDL 36 AA, SIGRACET® from SGL Carbon GmbH) with a thickness of 225 μm (measured at a load of 5 psi) is coated on one side with an epoxy resin film (2) with a thickness of 180 μm, in which 10% by weight of filler is dispersed in the epoxy resin. The 10% by weight is composed of conductive carbon black (Super P available from Imerys) and expanded graphite (Sigratherm® GFG5 available from SGL Carbon) in a ratio of 70:30. The coated monolayer is then cured in a hot press at a pressure of 32.5 bar and 130° C. for 60 minutes.

[0053] At a surface pressure of 1MPa contact Resistance is 6.2mΩcm 2 The transmission coefficient is 2.2×10 -6 cm 2 / s. The thickness of the separator plate thus obtained is 220 μm (measured at a load of 5 psi). The geometric density is 1.18 g / cm 3 It is.

[0054] EMBODIMENT 5 A monolayer of carbon fiber reinforced carbon (1) (available under the name GDL 36 AA, SIGRACET® from SGL Carbon GmbH) with a thickness of 225 μm (measured at a load of 5 psi) is coated on one side with an epoxy resin film (2) with a thickness of 180 μm, in which 10% by weight of filler is dispersed in the epoxy resin. The 10% by weight is composed of conductive carbon black (Super P available from Imerys Graphite & Carbon) and expanded graphite (Sigratherm® GFG5 available from SGL Carbon) in a ratio of 30:70. The coated monolayer is then cured in a hot press at a pressure of 32.5 bar and 130° C. for 60 minutes.

[0055] At a surface pressure of 1MPa contact Resistance is 8mΩcm 2 The transmission coefficient is 3.7×10 -6 cm 2 / s. The thickness of the separator plate thus obtained is 208 μm (measured at a load of 5 psi). The geometric density is 1.04 g / cm 3 It is.

[0056] Embodiment 6: A monolayer of carbon fiber reinforced carbon (1) (available under the name GDL 36 AA, SIGRACET®, from SGL Carbon GmbH) with a thickness of 225 μm (measured at a load of 5 psi) is coated on one side with a 180 μm thick epoxy resin film (2) using a film applicator, with 7% by weight of conductive carbon black (Super P, available from Imerys Graphite & Carbon) dispersed in the epoxy resin. The coated monolayer is then cured in a hot press at a pressure of 10 bar and 130° C. for 60 minutes.

[0057] At a pressure of 1MPa contact Resistance is 5.4mΩcm 2 The transmission coefficient is 3.9×10 -6 cm 2 / s. The thickness of the separator plate thus obtained is 205 μm (measured at a load of 5 psi). The geometric density is 1.15 g / cm 3 It is. [Explanation of symbols]

[0058] 1 Single layer of carbon fiber reinforced carbon 2 thermosetting resin 3. Filler 4 Separator Plate

Claims

1. A separator plate comprising a single layer of carbon fiber reinforced carbon impregnated with a thermosetting resin, having a continuous conductive carbon network, the separator plate having a thickness of less than 0.5 mm and a tensile strength of greater than 30 MPa.

2. 8mΩcm 2 10. The separator plate of claim 1 having a contact resistance of less than 1000 nm.

3. 1.7 g / cm 3 3. The separator plate of claim 1 or 2 having a density of less than 1000 nm.

4. 10. The separator plate of claim 1, wherein the carbon fiber reinforced carbon comprises a single layer of woven carbon fiber having carbon-binder bridges between the carbon fibers.

5. 3. The separator plate of claim 1 or 2, wherein the thermosetting resin comprises a resin selected from the group consisting of epoxy resins, phenolic resins, furan resins, and benzoxazine resins.

6. The separator plate of claim 1 or 2, wherein the thermosetting resin includes a dispersed filler.

7. The separator plate according to claim 5 or 6, wherein the mass fraction of the filler is more than 0 mass% and not more than 40 mass%.

8. 5×10 -5 cm 2 3. The separator plate of claim 1, having a permeability coefficient, measured according to DIN 51935:2019-06, of less than 1.0 μm / s.

9. 3. The separator plate according to claim 1, wherein the surface of the carbon fiber reinforced carbon impregnated with the thermosetting resin is structured.

10. The separator plate of claim 6 or 7, wherein a cross-section of the separator plate has a filler concentration gradient.

11. 10. A method for manufacturing the separator plate of claim 1, comprising the steps of: Step a) of providing a carbon fiber fabric; Step b. impregnating the carbon fiber fabric with a carbon donor; Step c: subjecting the impregnated carbon fiber fabric to a high temperature treatment in an inert gas atmosphere at a temperature higher than 1300° C.; a step d of providing a thermosetting resin; step e) of impregnating the carbon fiber reinforced carbon obtained in step c) with the thermosetting resin provided in step d); and step f. curing and pressing the resin impregnated carbon fiber reinforced carbon from step e. under a pressure of 1-50 bar.

12. 12. The method of claim 11, wherein following step f, the surface is activated by grinding on both sides, blasting, chemical treatment, or plasma treatment.

13. The method according to claim 11 or 12, wherein greater than 0% and up to 40% by weight of a filler is dispersed in the thermosetting resin.

14. The method according to claim 11 or 12, wherein the pressing step is performed with a structuring tool.

15. The use of a separator plate according to any one of claims 1 to 10 in a redox flow battery or fuel cell or as an electrode for an electrostatic air purification device.

Citation Information

Patent Citations

  • Carbon fiber electrode substrate for electrochemical cells

    EP1369528A1